Pantao Pill Improves the Learning and Memory Abilities of APP/PS1 Mice by Multiple Mechanisms - Xin, Qiqi; Shi, Weili; Wang, Yan; Yuan, Rong; Miao, Yu; Chen, Keji; Cong, Weihong (Frontiers in Pharmacology, 2022)
Background: To explore the effect and mechanisms of Pantao Pill (PTP) on cognitive impairment. Methods: Network pharmacology was performed to analyze the mechanism of PTP treating cognitive impairment. The targets of PTP and cognitive impairment were predicted and used to construct protein-protein interaction (PPI) networks. The intersection network was selected, and the core network was obtained through topological analysis. Enrichment analysis was conducted to obtain the GOBP terms and KEGG pathways. We then performed experiments to validate the results of the network pharmacology by using an APP/PS1 transgenic mouse model. The APP/PS1 mice were divided into four groups: the model group, the high-dose PTP (3.6 g/kg·d) group, the low-dose PTP (1.8 g/kg·d) group, and the positive control group (donepezil hydrochloride, 2 mg/kg·d). Wild-type (WT) C57 mice served as a normal control group. PTP and donepezil were administered by gavage for eight weeks. Results: Network pharmacology showed that PTP might improve cognitive impairment by regulating autophagy, apoptosis, and oxidative stress. For the Morris water maze test, a significant difference was shown in the total swimming distance among groups (P<0.05) in the positioning navigation experiment, and with training time extension, the swimming speed increased (P<0.01). In the space probe test, PTP administration significantly reduced the swimming path length and the escape latency of APP/PS1 mice (P<0.05 or P<0.01), whereas it had no effect on the swimming speed (P>0.05). PTP (3.6g/kg/d) rescued the reduction of norepinephrine and acetylcholine levels (P<0.05), and increased the acetylcholinesterase concentration (P<0.05) in the brain tissue. PTP (1.8g/kg/d) increased the norepinephrine level (P<0.05). PTP rescued the activity reduction of superoxide dismutase in the brain tissue (P<0.05) and the neuron cell pyknosis in the hippocampal CA region (P<0.01). PTP reduced ATG12 and PS1 expression (P<0.05 or P<0.01), and increased Bcl-2 expression in the brain tissue (P<0.05). Conclusion: PTP can significantly improve the learning and memory abilities of APP/PS1 mice, and the mechanism may be related to the improvement of neurotransmitter Ach and NE secretion, the reduction of the excessive autophagic activation, and the suppression of oxidative stress and excessive autophagic activation.